Rheumatoid-like hand deformities and aortic valve disease in a 13-year-old girl with homozygous familial hypercholesterolemia: a case report - Anjuman Ara Rahman; Abhijit Datta; Kamal Uddin Ahmed; Anindita Das Barshan; Mohammad Jahid Hasan (Journal of Medical Case Reports)
Abstract Background Familial hypercholesterolemia is an autosomal dominant disorder characterized by elevated serum low-density lipoprotein cholesterol levels, tendon xanthomas, and an increased risk of atherosclerotic heart disease. Diagnosing familial hypercholesterolemia at an early age is crucial owing to its potential to lead to severe cardiovascular complications, including coronary heart disease and aortic valve disease. Early detection allows timely intervention, such as lifestyle modifications and pharmacological treatments, which can significantly reduce these risks. Case presentation In this case report, we present a case of familial hypercholesterolemia in a 13-year-old Bangladeshi girl residing in Faridpur, Bangladesh. The patient presented with a distinctive clinical profile, including the presence of tendon xanthoma in the hands and cutaneous xanthoma in the elbow, knee, and buttocks, as well as recent development of aortic valvular diseases. In addition, she experienced joint deformity in both hands, mimicking rheumatoid arthritis, which is uncommon. The patient was diagnosed and underwent treatment through both lifestyle changes and medication. Moreover, her family received genetic counseling, and she was scheduled for regular follow-up. Conclusion This case underscores the significance of identifying important physical signs in the diagnosis and management of familial hypercholesterolemia, particularly in settings where genetic testing may be limited. Moreover, the unique coexistence of familial hypercholesterolemia with hand joint deformity and aortic valvular heart disease serves as a clinical clue that can facilitate diagnosis and appropriate therapeutic interventions. A high index of suspicion is essential for timely diagnosis and tailored management, thus reducing the burden of atherosclerotic heart disease in affected individuals.